TENDENCIES OF THE HUMANIZATION OF SCHOOL EDUCATION IN RUSSIA AND ABROAD - Tatiana Alexandrovna Chibisova (Erudio Journal of Educational Innovation, 2018)
In the article the essence of the concept "humanization" of education is considered, the main regularities of this process are given, the main vector of humanization of education in Russia is defined. Also in the article characteristic changes which have concerned each component of the educational environment of Great Britain in the context of process of humanization are analyzed.